Study on Food Loss and Food Waste: Conditions, Impact and Solutions - Mitha Ayu Pratama Handoyo; Nyoman Puspa Asri (UNIVED Press, Dehasen University Bengkulu, 2023)
The purpose of writing this article is an attempt to introduce readers to the problem of Food Loss & Food Waste (FL&FW) in a comprehensive concept regarding conditions, impacts and solutions for handling them. FL&FW has been a global issue for a long time, but until now its impact is getting more serious. The losses incurred by FL&FW are not only in the environmental field but are very complex including economic and social losses. Food and Agriculture Organization/FAO has estimated that 1/3 of world food production or around 1.3 billion tons which is equivalent to 990 billion USD has been lost in vain. But on the other hand, about 21,000 people die every day because of hunger. This topic will continue to be a central issue in the coming years, because the amount of food that must be provided will also continue to increase in line with the increasing world population and the problems caused by the Co-19 pandemic. Reducing food waste is a priority scale to maintain sustainable food security. The FL&FW issue since 2015 has been one of the programs of the Sustainable Development Goals (SDGs), on target 12.3 with a commitment to reduce food waste by half per capita by 2030. Therefore, all stakeholders (government, industry and society) must collaborate to implementing policies and cultural changes towards prevention of FL&FW on all fronts.